The website content as positioning strategy of the university in indonesia - Amida Yusriana; Mutia Rahmi Pratiwi; Lisa Mardiana (IAIN Salatiga, 2020)
University of Indonesia is granted as the number one campus based on the Webometrics rank. It cannot be separated from the way University of Indonesia in building a strategic content for its website thus can fulfill the four points score indexes of webometrics such as Presence, Impact, Openness, and Excellence. Never theless the way the website serves the menu and information can build the right point of the scores. At the same time, Dian Nuswantoro University is granted as the 31st rank for the Webometrics index. Hence, by analyzing the website content of University of Indonesia, later it can be a guideline for Dian Nuswantoro University in developing a better content. This research uses the Positioning Strategy Theory. This is a descriptive quantitative research with a content analysis method. The results shows that the University of Indonesia uses the functional concept positioning strategy as its website content strategy.